Biomarkers in cardiovascular medicine: towards precision medicine (Swiss Medical Weekly, 2019)
Biomarkers are noninvasive, inexpensive, highly reproducible tools that allow clinicians to quantify pathophysiological processes relevant to a specific disease. Although the concept of biomarker-guided precision medicine is still in its infancy once a specific cardiovascular diagnosis is established, biomarker guidance has become the standard of care in the early diagnosis of acute cardiovascular disease in patients presenting to the emergency department with common symptoms such as acute chest pain or acute dyspnoea. This review highlights recent advances and remaining uncertainties regarding the use of the most relevant cardiovascular biomarkers, namely high-sensitivity cardiac troponin and natriuretic peptides in established indications such as the early diagnosis of acute myocardial infarction and heart failure. In addition, we address emerging indications such as the screening for perioperative myocardial infarction.